Diatom Similarity in Experimental Drowning of Rattus norvegicus as Forensic Evidence for Determining The Drowning Site - Hidayatulloh, Taufik; Nofrita, Nofrita; Nurdin, Jabang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Diatom analysis is one of the most reliable indicators for confirming death due to drowning. Diatoms are microscopic algae that can enter the respiratory tract during water aspiration and provide ecological evidence linking the victim to the drowning site. This study aimed to analyze the presence of diatom species and taxonomic similarity between water samples and the internal organs of experimentally drowned white rats (Rattus norvegicus) to validate their use as a forensic model. Experimental drowning was performed using water of the Batang Arau River, West Sumatra in the February 2024 to January 2025. In this study, we were found 56 species of diatoms in the waters, while 31 were found in white rats' internal organs. The highest diversity found in the esophagus (31 species) and lungs (19 species). No diatoms were detected in the heart, liver, or kidneys. The distribution pattern, limited to the respiratory system, indicated early drowning aspiration with no systemic circulation. The typical species is a diatom species only found in water and in the internal organs of white rats in specific locations. Achnanthes adnata, Cocconeis pellucida, Cocconeis pseudomarginata, Eunotia bilunaris, and Gomphonema pumilum are typical species at Location I. Amphora bigibba and Amphora bioculata are typical species at Location IV. At the same time, Navicula viridula is the typical species at Location VI. These findings validate the white rat as an effective experimental model for drowning research and demonstrate that species-specific diatom fingerprints can aid forensic investigators in determining both the vitality of drowning and the probable crime scene.